Modelling of pandanus amaryllifolius plant-microbial fuel cell as low power generation source with energy yield enhancement - Teng, Howe Cheng (2020)
Research on alternative renewable energy resources that are pollution-free have been conducted since last decade, whereas the existing conventional energy resources are depleting. Among the emerging energy resources is living plants energy. However, plant-based energy harvesting technology is still not well optimised and has low energy generation that needs to be improved, leading to this proposed project. In order to achieve the objectives, characteristics of Pandanus Amaryllifolius plant-microbial fuel cell has been investigated. A study to improve its electrical generation under a series of experimentation works, where the relationship between substrate and oxidation agent in controlled and uncontrolled environment have been investigated. A predictive model has been developed based on the retrieved experimental data. From the experimental works, the inoculated plant microbial fuel cell is optimised to an average voltage output of 0.598 ± 0.008 V and power output of 2.867 mW with cathode electrode area implementation of 10000 mm2 . Besides, the internal resistance of the fuel cell has been reduced to 123.96 ± 2.68 Ω, which is a reduction of 624% as compared to the fuel cell with the smallest cathode area, achieving a coulombic efficiency of 64.63%. Furthermore, a predictive mathematical model with adjustable parameters such as temperature, light intensity, sun elevation angle, acetate rhizodeposition rate/ concentration, bacteria concentration, membrane area, electrode area and substrate flow rate has been developed. With the proposed models, the generation of voltage, current and power from Pandanus Amaryllifolius P-MFC can be predicted with plant rhizodeposition model of less than 5% error and bacteria growth model achieving high similarity with power output. Finally, an energy harvesting circuit has been proposed with a minimum input voltage of 0.45 V. From the test, 0.612 mV of input voltage has been boosted up to 1.47 V. By achieving all the objectives, the well optimised plant-microbial fuel cell is deemed to take a leap to be applied in the real-life applications such as in IoT and electricity generation in remote areas.